Humor and YouTube: Do Perceived Realism and Homophily Change What is Funny? - Gustafson, Kelsey; Roberts, Rachel; Powers, Lizzie; Washleski, Rebecca (My University, 2009)
Created in 2005, YouTube has become the most successful video streaming site on the Internet. Because it is universally available, reaches millions of people, and is uncontrolled, YouTube may be a powerful persuasive force in society. Yet, little is known about its effects. This study seeks to explore the relationship between homophily, perceived realism, and viewers' judgments of humor quality in YouTube videos.
Color poster with text, images, tables, and graph.
Keywords: YouTube (Electronic resource); Streaming video--Humor; Wit and humor--Psychological aspects; Wit and humor--Social aspects; Posters